ANALYSIS OF THE «CLOUDY» BUSINESS-MODEL ON THE EXAMPLE OF BUILDING MANAGEMENT SYSTEMS - A. Dashkov; A. Makarov (Вестник университета)
Today the corporate IT-market also was added to the purposes of a cloud computing in Russia, besides the consumer market. On corporate B2B the market a cloud computing can provide additional value for clients, but they are more conservative and therefore apply new technologies more slowly. Article represents the analysis of model of cloudy business and considers a business model of cloud computing on the example of the market of management of buildings, new to Russia. A cloud computing became mature, opportunities for the solution of problems at the different organizational levels increased. Article creates a basis for representation of the general models of the B2B-clouds promoting effective development of business models of B2B for other industrial cloudy offers.